The Effect of Temulawak Extract (Curcuma xanthorrhiza Roxb.) on the Growth of Escherichia coli - Shania Eugene Sutopo; Retno Budiarti; Chonifa Wahyurini (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Indonesia is a developing country that still faces many infectious diseases affecting its population, with one of the most common causes being the bacterium Escherichia coli. Antibiotics are used to treat bacterial infections; however, the increasing cases of antibiotic resistance in Indonesia have become a concerning public health issue. Temulawak (Curcuma xanthorrhiza Roxb.) is a traditional plant containing active compounds—especially flavonoids, xanthorrhizol, and curcumin—that possess antibacterial activity, making it a potential agent to inhibit the growth of Escherichia coli. Objective: To determine the effect of temulawak (Curcuma xanthorrhiza Roxb.) extract on the growth of Escherichia coli. Method: The inhibition of Escherichia coli growth was tested on Mueller Hinton media using the disc diffusion method. There were six treatment groups: negative control (sterile distilled water), positive control (Ciprofloxacin 500 mg), and extract concentrations of 25%, 50%, 75%, and 100%, each with four repetitions. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney U test. Result: The positive control showed an average inhibition zone diameter of 50.6 mm; 100% concentration: 10.6 mm; 75%: 10.2 mm; 50%: 8.90 mm (moderate inhibition); 25%: 7.52 mm; negative control: 6.00 mm. The Kruskal-Wallis test indicated a significant difference among the six groups with a significance value of 0.001 (p < 0.005). Conclusion: Temulawak (Curcuma xanthorrhiza Roxb.) extract at 100% concentration is the most effective treatment group in inhibiting the growth of Escherichia coli.